Analisis Kuantitatif Statistik Asuhan Kesehatan Rumah Sakit Islam Siti Rahmah Padang - Aulia Sixta Vernanda (Iris Journal of Health Information Management, 2022)
Research at RSI SITI RAHMAH Padang can be used as a basis for hospitals in decision making, policy making so as to improve service quality. This study aims to determine the quantitative statistical analysis of inpatient health care at RSI SITI RAHMAH Padang. Data collection was carried out by direct observation at the medical record section in May 2021 at RSI SITI RAHMAH Padang, data obtained as many as 728 patients went home, with a total of 179 beds. From the main grouping of diagnoses based on ICD-10, there was a diagnosis of Delivery by caesarean section with code O82.9 as many as 35 patients, based on defecation on ICD-10, the highest diagnosis grouping was CHAPTER XV (Pregnancy, Childbirth And The Puerperium) with a percentage of 12 ,08% as many as 88 patients, the most procedures were Caesarean Section with a procedure code of 74.99 as many as 60 patients, the highest DTD code and definition was DTD 242.9 Pregnancy and Other Childbirth Diseases with a total of 44 patients. From the RL4a report, the most gender groupings were female patients as many as 405 patients and male patients as many as 323 patients, the disposition of living patients was 720 patients, while those who died were 8 patients. 93 patients. Based on the results of statistical data processing of health care concluded that BOR, BTR and TI are efficient.